Detection of a New Tert-Leucinate Synthetic Cannabinoid 5F-MDMB-PICA and Its Metabolites in Human Hair: Application to Authentic Cases - Shi, Yan; Zhou, Liying; Li, Le; Liu, Mengxi; Qiang, Huosheng; Shen, Min; Shen, Baohua; Chen, Hang; Drummer, Olaf H.; Liu, Wanhui; Wu, Hejian; Xiang, Ping (Frontiers in Chemistry, 2020)
Methyl 2-[[1-(5-fluoropentyl)indole-3-carbonyl]amino]-3,3-dimethyl-butanoate (5F-MDMB-PICA) is a new synthetic cannabinoid characterized by valinate or tert-leucinate moieties. In recent years, 5F-MDMB-PICA has been abused in the form of “spice-like” herbal incenses or electronic cigarette oil. A UHPLC-MS/MS method was developed to detect 5F-MDMB-PICA and its metabolites in human hair. Approximately 20 mg of hair was weighed and pulverized with methanol below 4 °C. After ultrasonication, centrifugation and filtration, 200 µL of supernatant was placed into an autosampler vial and analysed on a Waters Acquity UPLC HSS T3 column (100 mm 2.1 mm, 1.8 m particle size) using an acetonitrile-20 mmol/L ammonium acetate (0.1 % formic acid, 5 % acetonitrile) gradient with a run time of 8 min. The limit of detection (LOD) ranged from 0.5 to 5 pg/mg, and the lower limit of quantitation (LLOQ) ranged from 1 to 5 pg/mg. The method was shown to be linear over a concentration range of 1-200 pg/mg. The linear correlation (R2) of the calibration curves for all analytes was 0.999. The accuracy varied from 95.4 % to 107.4 %, while the intra- and inter-day precision RSD values were 0.7-10.6 % and 1.7-12.2 %, respectively. Recoveries were within the range of 61.1-93.3 %, and matrix effects were in the range of 19.1-102.6 %. The validated method was successfully applied to the identification and quantification of 5F-MDMB-PICA and its metabolites in hair from authentic forensic cases.